Adaptive response in waterbirds after mink introduction in subantarctic ecosystems - Valeria Gómez-Silva; Fabian M. Jaksic; Ramiro D. Crego; Gabriela Flores-Benner; Elke Schüttler (Scientific Reports)
Abstract Ground-nesting birds on islands are particularly vulnerable to the introduction of terrestrial carnivores because the former often lack defensive behaviors, displaying high levels of naivety under absence of co-evolutionary history. Relatively few studies have addressed such potentially adaptive responses. In this study, we investigated whether two bird species, upland geese (Chloephaga picta) and flightless steamer ducks (Tachyeres pteneres) have modified their nesting strategies as a response to the novel predatory pressure imposed by the invasive American mink (Neogale vison) on Navarino Island, southernmost Chile, since its arrival in 2001. We used discriminant analysis and pairwise Wilcoxon tests to compare two data sets (n = 140 nests in total) regarding the macro- and microhabitat where nests were placed, separated by a time span of 15 years. We found that upland geese currently nest in less dense habitat (macrohabitat), hide their nests in shorter shrubs with lower top and side cover (microhabitat), and breed later in the season. In contrast, flightless steamer ducks retain almost the same nesting habitat characteristics. We discuss our findings in the context of ecological and evolutionary restrictions to adaptation.